Effect of Roller Burnishing on the Mechanical Behavior and Surface Quality of AISI 316 Stainless Steels - Uenal, Engin; Albar, Hilal Buesra; Karaca, Faruk (Springer, 2026)
Roller burnishing has recently gained popularity as a cost-effective and efficient surface finishing technique. In this process, a rolling element is pressed against the surface with a specific amount of force, causing plastic deformations that improve surface roughness without removing material. As a result, the method significantly reduces surface roughness while increasing the surface hardness of the material. This technique offers an economical solution by enhancing surface quality and eliminating material loss. In this study, specimens made of AISI 316 austenitic stainless steel were subjected to roller burnishing. For roller burnishing application, force, pass and feed rate parameters were varied at three different levels. The processes were applied to the samples according to the determined parameters, and the effects of the parameters on the microhardness, tensile strength, diameter changes, and roughness values of the samples were determined experimentally. In the experiments, it is seen that the best surface roughness value after the roller burnishing process was measured as 0.100 mu m. It was determined that the roller burnishing process caused an increase in the microhardness values of the sample walls in general, and the microhardness value increased with the increase in the number of passes and feed rate. On the other hand, it was also determined that the diameter change increased with increasing load and number of passes.
Keywords: austenitic stainless steel; mechanical properties; roller burnishing; surface roughness; tensile test